2009
DOI: 10.1093/humrep/dep222
|View full text |Cite
|
Sign up to set email alerts
|

Is there a uniform basal endometrial gene expression profile during the implantation window in women who became pregnant in a subsequent ICSI cycle?

Abstract: Our data suggest that very few genes, which change their expression level during the WOI, show a quantitative homogeneous expression in endometrially-receptive patients. In conclusion, in this study only six genes showed a homogeneous expression, and are probably involved in embryo implantation mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Although functional analysis and studies in knockout mice have demonstrated that all not these genes have a role in the embryonic implantation process (48), they are unquestioned markers of the correct functioning of the endometrium. Indeed, LIF expression has been shown to be statistically uniform among patients who subsequently became pregnant in intracytoplasmic sperm injection cycles (49). We have also detected the dysregulation of other genes, such as CAPN6 and HABP2 in obese women with PCOS, which have recently been shown to be dysregulated during the WOI in women with unexplained infertility (50).…”
Section: Discussionmentioning
confidence: 57%
“…Although functional analysis and studies in knockout mice have demonstrated that all not these genes have a role in the embryonic implantation process (48), they are unquestioned markers of the correct functioning of the endometrium. Indeed, LIF expression has been shown to be statistically uniform among patients who subsequently became pregnant in intracytoplasmic sperm injection cycles (49). We have also detected the dysregulation of other genes, such as CAPN6 and HABP2 in obese women with PCOS, which have recently been shown to be dysregulated during the WOI in women with unexplained infertility (50).…”
Section: Discussionmentioning
confidence: 57%
“…This characteristic profile suggested that a unique transcriptional process occurs to achieve a receptive phenotype (Borthwick et al 2003;Riesewijk et al 2003;Horcajadas et al 2008;Haouzi et al 2009a,b; The implantation of the blastocyst in the endometrium activates the production of cytokines that modulate receptivity by regulating the expression of adhesion molecules in mammals (Simon et al 1997). Leukemia inhibitory factor (LIF) is a cytokine that has been the focus of many studies (Aghajanova et al 2008;Allegra et al 2009;Rashid et al 2011) because of its clear functional effect in the mouse model. Osteopontin (SPP1) has been the gene with the greatest consensus among most endometrial transcriptomic studies.…”
Section: Transcriptomics Of Endometrial Receptivitymentioning
confidence: 99%
“…STC is expressed in pre-pregnancy endometrium and early pregnancy decidua in rats and pigs, is regulated by estrogen and progesterone, and has been suggested as an implantation marker in pig endometrium (1, 2). In humans, consistent mid-secretory endometrial (MSE) STC1 gene expression was demonstrated in patients who conceived with the help of assisted reproductive technologies (ART) (3). STC1 was significantly upregulated in microarray analysis of MSE of the normal menstrual cycle compared to early secretory endometrium (ESE) (4), and was down-regulated in microarray analysis of MSE from women with unexplained infertility versus fertile control subjects (5), suggesting a possible role in human endometrial receptivity and implantation.…”
Section: Introductionmentioning
confidence: 99%